Radio frequency identification and IoT security : 12th International Workshop, RFIDSec 2016, Hong Kong, China, November 30-December 2, 2016, Revised selected papers /: 12th International Workshop, RFIDSec 2016, Hong Kong, China, November 30-December 2, 2016, Revised selected papers. (2017) - Unknown
No abstract available